2016
DOI: 10.18865/ed.26.4.485
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Body Fat and Leisure Time Physical Activity Called into Question for Asian Indians

Abstract: Objective: Thrifty genotypes may predispose to type 2 diabetes and body fat (%BF) excess through a differentiated relationship between physical activity and body fat. We explored this hypothesis in Asian Indians, a population thought to be thrifty. Methods:Three hundred and nine Guadeloupian adolescents responded to the modifiable activity questionnaire. Their body fat was assessed by bioimpedancemetry. We first studied the relationship between %BF and leisure time physical activity (LTPA). We then explored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…No significant difference in abdominal obesity (defined as elevated waist circumference) by ethnicity was found in adolescents in Jamaica (black versus non-black [reference]; 16) or Guadeloupe (17). In Suriname (18, 19), rates of abdominal obesity were highest among Amerindian indigenous populations (71.6%, 95%CI = 62.5 – 79.8; Creole 46.5%, 95%CI = 40.9 – 52.0; Hindustani 65.5%, 95%CI = 62.3 – 68.6; Javanese 52.3%, 95%CI = 47.4 – 57.1; Maroon 52.2%; 95%CI = 47.4 – 57.1; Mixed 60.1%; 95%CI = 54.9 – 65.0).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant difference in abdominal obesity (defined as elevated waist circumference) by ethnicity was found in adolescents in Jamaica (black versus non-black [reference]; 16) or Guadeloupe (17). In Suriname (18, 19), rates of abdominal obesity were highest among Amerindian indigenous populations (71.6%, 95%CI = 62.5 – 79.8; Creole 46.5%, 95%CI = 40.9 – 52.0; Hindustani 65.5%, 95%CI = 62.3 – 68.6; Javanese 52.3%, 95%CI = 47.4 – 57.1; Maroon 52.2%; 95%CI = 47.4 – 57.1; Mixed 60.1%; 95%CI = 54.9 – 65.0).…”
Section: Resultsmentioning
confidence: 99%
“…In Suriname (18, 19), rates of abdominal obesity were highest among Amerindian indigenous populations (71.6%, 95%CI = 62.5 – 79.8; Creole 46.5%, 95%CI = 40.9 – 52.0; Hindustani 65.5%, 95%CI = 62.3 – 68.6; Javanese 52.3%, 95%CI = 47.4 – 57.1; Maroon 52.2%; 95%CI = 47.4 – 57.1; Mixed 60.1%; 95%CI = 54.9 – 65.0). In addition, obesity measured by BMI (both as a continuous variable and as a prevalence ≥ 30kg/m 2 ) was described by ethnicity in 9 relationships across 7 studies: in Jamaica (16), Guadeloupe (17, 20), Suriname (18, 19), Trinidad and Tobago (21), and Barbados and Cuba (22). Studies found no significant differences in rates of obesity among black Jamaican adolescents (odds ratio [OR]: 1.03; 95%CI = 0.55 – 1.93), or among black adults in Barbados and Cuba combined (OR:1.33; 95%CI = 0.97 – 1.81) when compared to “white” (term used in the sources) subjects (16, 22).…”
Section: Resultsmentioning
confidence: 99%